Harvesting of Living Cell Sheets by the Dynamic Generation of Diffractive Photothermal Pattern on PEDOT. (24th January 2017) - Na, Jongbeom; Heo, June Seok; Han, Minsu; Lim, Hanwhuy; Kim, Hyun Ok; Kim, Eunkyoung
Abstract : Near infrared (NIR) photothermal pattern on conductive polymer film enables unique approaches to harvest large‐area cell sheets with various patterns without the use of patterned culture dish. The NIR photothermal pattern is generated from a patterned optical lens (POL), which creates a dynamic near IR light pattern and the corresponding photothermal pattern (PTP) on the polymer film. The POL is prepared from transparent polydimethylsiloxane designed to generate various light patterns. The PTPs allow a noninvasive harvest of cultured cells as an intact living cell sheet with a high harvesting efficiency (ηcell > 100). Various PTPs are generated by the diffraction of NIR light through POLs having different micropatterns, which afford cell sheets with a desired pattern without changing the original cell morphology at cultured state. Furthermore, a large‐area living cell sheet is obtained with a detached area larger than 19 cm 2, which is the largest living cell sheet up to date. Further optical engineering of the harvesting system allows multiple productions of cell sheets with one dose of light. It is possible to harvest cell sheets not only from human fibroblast cells but also from human adipose‐derived stem cells, indicating that the method can be applied to engineer various cells. Abstract : Through a dynamic control of near infrared light diffraction, the photothermal patterns are generated onto the poly(3, 4‐ethylenedioxythiophene) surface with various patterns such as line, square, and hexagonal. This optical method can harvest not only the patterned and large‐area cell sheets but also multiple cell sheets at once.